Answer:
Hey there! The correct answer would be x=-4.
Step-by-step explanation:
To start, you would first need to combine your like terms, terms that are not only raised to the same power but also have the same exact variables. In this case, your like terms are -6x and -11x:
-6x-11x=68 --> -17x=68
Now, divide both sides by -17 in order to isolate your variable term:
-17x/-17 = 68/-17
x=-4
Therefore, your answer would be x=-4.
To check to make sure this answer is right, plug -4 in for x and see if the result is 68=68:
-6(-4)-11(-4)=68
24+44=68
68=68
Hope this helps! :)